Lissencephaly in Shih Tzu dogs - Rodríguez-Sánchez, Diego Noé [UNESP]; Pinto, Giovana Boff Araujo [UNESP]; Thomé, Edval Fernando [UNESP]; MacHado, Vânia Maria De Vasconcelos [UNESP]; Amorim, Rogério Martins [UNESP] (Springer Nature, 2020)
Background: Lissencephaly is a brain malformation characterized by smooth and thickened cerebral surface, which may result in structural epilepsy. Lissencephaly is not common in veterinary medicine. Here, we characterize the first cases of lissencephaly in four Shih Tzu dogs, including clinical presentations and findings of magnetic resonance imaging of lissencephaly and several concomitant brain malformations. Case presentation: Early-onset acute signs of forebrain abnormalities were observed in all dogs, which were mainly cluster seizures and behavioral alterations. Based on neurological examination, the findings were consistent with symmetrical and bilateral forebrain lesions. Metabolic disorders and inflammatory diseases were excluded. Magnetic resonance imaging for three dogs showed diffuse neocortical agyria and thickened gray matter while one dog had mixed agyria and pachygyria. Other features, such as internal hydrocephalus, supracollicular fluid accumulation, and corpus callosum hypoplasia, were detected concomitantly. Antiepileptic drugs effectively controlled cluster seizures, however, sporadic isolated seizures and signs of forebrain abnormalities, such as behavioral alterations, central blindness, and strabismus persisted. Conclusions: Lissencephaly should be considered an important differential diagnosis in Shih Tzu dogs presenting with early-onset signs of forebrain abnormalities, including cluster seizures and behavioral alterations. Magnetic resonance imaging was appropriate for ante-mortem diagnosis of lissencephaly and associated cerebral anomalies.
Keywords: Agyria; Arachnoid cysts; Malformation of cortical development; Pachygyria; Seizures